Changes of physical mobility among patients with cognitive disorders provided with long-term institutional care in Poland - Kuźmicz, Ilona; Brzostek, Tomasz; Górkiewicz, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. Demographic changes in European countries result in population aging, higher number of people with disabilities and chronic illness, thus lead to an increase in demand for care services. Currently there are no Polish publications and limited international works dealing with the evaluation of needs of long term care persons with cognitive disorders and other coexisting diseases. Aim. Assessment of physical mobility changes among patients with cognitive disorders provided with long-term institutional care in Poland. Material and methods. Study involved 160 persons with cognitive disorders (125 women and 35 men), age between 61–100 years. The study group included 80 patients of long-term care institution and 80 inhabitants of the social welfare home. The standardized Cognitive Assessment Scale (CAS) and the Barthel scale were used as the research tools. Results and conclusion. The analysis of physical mobility changes revealed that mean values did not show significant differences (p > 0.005) in either of the institution. However, high individual variability of physical mobility was observed. Some patients’ health condition deteriorated significantly. Presented results indicate that patients with cognitive disorders provided with a long-term stationary care show diversified physical mobility in each of analyzed institution. These patients need individual and systematic assessment, which is a principal condition to provide an adequate long-term care in institutional settings. Nursing Topics 2014; 22 (2): 154–158